2011
DOI: 10.1097/gco.0b013e328348a245
|View full text |Cite
|
Sign up to set email alerts
|

The role of laparoscopic myomectomy in the management of uterine fibroids

Abstract: Laparoscopic myomectomy cases are mostly doable, but may become difficult if bleeding problems occur. Extended operative times may be required for morcellation and extensive laparoscopic suturing. Gynecologists need to improve their laparoscopic skills, as minimally invasive surgery is becoming the sine qua non of a modern surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…The prevalence of myomas within this specific population of women is 20–50%. [1] Within the infertile population, the incidence of myomas has been reported to be 5–10%; indeed, it has been reported that myomas serve as the sole factor underlying infertility in 1–2.4% of cases. [234]…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of myomas within this specific population of women is 20–50%. [1] Within the infertile population, the incidence of myomas has been reported to be 5–10%; indeed, it has been reported that myomas serve as the sole factor underlying infertility in 1–2.4% of cases. [234]…”
Section: Introductionmentioning
confidence: 99%
“…Myomectomy is the most common conservative treatment in gynecology, performed by classical open surgery or by laparoscopy. 4 There is support for performing myomectomy by removing the fibroid from its surrounding structure, the fibroid pseudocapsule, 5 an “intracapsular myomectomy.” It is performed by stretching and extracting fibroid tissue directly from the surrounding fibromuscular skeleton, breaking up the fibrous bridges. The importance of intracapsular myomectomy was described in a recent review.…”
Section: Introductionmentioning
confidence: 99%
“…1 Myoma is mostly asymptomatic. Size and location are the main factors that determine if a myoma leads to symptoms and problems.…”
Section: Introductionmentioning
confidence: 99%